2020
DOI: 10.37899/journallabisecoman.v1i5.234
|View full text |Cite
|
Sign up to set email alerts
|

Application of Probit Analysis in the Decision of Youths to Participate in Vegetable Production

Abstract: Youths are successor farming generation and therefore the future of food security. At present, they constitute about 60% of Nigeria’s population and have over the years contributed significantly to national development. Unfortunately, the present environment makes it  difficult to explore their full potentials in  production through participation in agriculture. The ageing smallholder farmers are less likely to increase capacity needed to sustainably expand agricultural production. There is therefore a pressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
(13 reference statements)
3
4
0
Order By: Relevance
“…For instance, as education increases by 1 grade (level), the probability of youth participation in an agriculture enterprise decreases by 18%, holding other factors constant, while compared to those youths who have access to initial capital, the probability of youth participation in an agriculture enterprise decreases by 36% for those youth who lacked initial capital, holding other factors constant. A study by Etim et al [22] found similar results in Nigeria. However, studies by Martinson et al [34] from Ghana and Gitore et al [15] from Ethiopia found unalike results that indicated that the likelihood of youth participation in agriculture enterprises increased as the education level increased.…”
Section: Determinants Of Youth Participation In the Agriculturalsupporting
confidence: 54%
See 1 more Smart Citation
“…For instance, as education increases by 1 grade (level), the probability of youth participation in an agriculture enterprise decreases by 18%, holding other factors constant, while compared to those youths who have access to initial capital, the probability of youth participation in an agriculture enterprise decreases by 36% for those youth who lacked initial capital, holding other factors constant. A study by Etim et al [22] found similar results in Nigeria. However, studies by Martinson et al [34] from Ghana and Gitore et al [15] from Ethiopia found unalike results that indicated that the likelihood of youth participation in agriculture enterprises increased as the education level increased.…”
Section: Determinants Of Youth Participation In the Agriculturalsupporting
confidence: 54%
“…Even though the binary models have a quite alike cumulative normal function (probit) and the logistic function (logit) [13,20], Gujarati [21] has noted the main difference by demonstrating that the logistic function has a slightly fatter tail as compared to probit model distribution. In addition, different studies suggested that the use of the probit model is more advantageous due to its normal distributional nature of latent error terms [18,20,22,23]. Since our data resembles a normal distribution, the probit model was used among the alternative logit model to estimate the probability of youth participation in agricultural enterprises.…”
Section: Econometric Model Specificationmentioning
confidence: 99%
“…This might be related to the fact that younger individuals are more willing to try new things than older ones. It is consistent with findings by Ayamga (2006), Etim andEdet (2013a,2013b), Etwire et al,(2013), Etwire et al,(2017), Etim et al,(2020aEtim et al,( , 2020b, who discovered that teenagers were risk takers, responsive, and more inclined to accept innovations quicker than older individuals. However, this conclusion is in contrast to that of Asante et al (2011), who found that age had a favorable influence on farmers' decision-making.…”
Section: Factors Influencing Willingness Of Churches To Undertake Poverty Reduction Programssupporting
confidence: 91%
“…(3) For econometric estimation, linear probability model (LPM), Logit, Probit models suggested regression models by numerous for binary choice depended on variables [6,23,[31][32][33][34] . Since our dependent variable is dummy, the alternative binary models such as logit and probit models were used for this study.…”
Section: Analytical Frameworkmentioning
confidence: 99%